2018
DOI: 10.1002/aet2.10102
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Early Educational Intervention on Coding for First‐year Emergency Medicine Residents

Abstract: The focused longitudinal educational interventions resulted in improved billing performances, reflected by better documentation, in the intervention group versus the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
(10 reference statements)
1
10
0
Order By: Relevance
“…15,16 Another recent study found that resident education of billing practices significantly increased RVU billable by resident encounters. 17 Taken together, this body of literature suggests that educational interventions such as ours can have a quantifiable effect on ED revenue and future EP documentation practices.…”
Section: Discussionmentioning
confidence: 75%
“…15,16 Another recent study found that resident education of billing practices significantly increased RVU billable by resident encounters. 17 Taken together, this body of literature suggests that educational interventions such as ours can have a quantifiable effect on ED revenue and future EP documentation practices.…”
Section: Discussionmentioning
confidence: 75%
“…Some studies have identified that the inability to receive ultrasound expenses serves as a barrier to the use of POCUS [14,16]. In addition, some studies have shown that the frequency of ultrasound use has increased since the introduction of reimbursement claims or education on billing practices [19,27,28]. Adhikari et al identified that educational intervention in the billing process increased the number of POCUS scans billed by 180% [28].…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes Kern's framework, outlines key aspects of our curricular design, and includes supporting educational evidence. Based upon results of a few studies 3,6,7 , charting and coding education during residency is well received and has the potential to improve con dence and performance…”
Section: Curricular Designmentioning
confidence: 99%
“…skills. 2,3,4,5 While institutions have used multiple pedagogical approaches, the best method for teaching charting and coding is unknown. 6,7 To address the lack of a standardized charting and coding educational method at our institution, we incorporated charting and coding skills in our health policy curriculum.…”
Section: Introductionmentioning
confidence: 99%